2022
DOI: 10.1111/dmcn.15381
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of developmental delay in infants born very preterm or with very low birthweight

Abstract: Aim: This study aimed to identify early clinical biomarkers from birth to 16 weeks corrected age to predict typical outcome and developmental delay in infants born very preterm or with very low birthweight. Method:A prospective cohort of infants on the Sunshine Coast, Australia, was assessed using the Premie-Neuro Examination, the General Movement Assessment (GMA), the Alberta Infant Motor Scale, and the Infant Sensory Profile 2. At 24 months corrected age, delay was identified using the Bayley Scales of Infan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Consistent with this line of research, Caesar et al reported that the suboptimal quality of general movements (especially fidgety general movements at 16 weeks corrected age) had predictive accuracy of motor and cognitive delay at 2 years with high sensitivity in infants born very preterm/low birthweight 2 . Furthermore, the authors suggest that GMA trajectories that combined abnormal writhing general movements with the suboptimal fidgety movements are strong behavioral markers for predicting developmental delay.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Consistent with this line of research, Caesar et al reported that the suboptimal quality of general movements (especially fidgety general movements at 16 weeks corrected age) had predictive accuracy of motor and cognitive delay at 2 years with high sensitivity in infants born very preterm/low birthweight 2 . Furthermore, the authors suggest that GMA trajectories that combined abnormal writhing general movements with the suboptimal fidgety movements are strong behavioral markers for predicting developmental delay.…”
mentioning
confidence: 72%
“…First, the prediction of cognitive function through the GMA is still less accurate overall than that of cerebral palsy, and inconsistent across previous studies 1,2 . This lesser accuracy is assumed to reflect the diversity of cognitive dysfunctions and their etiologies, in addition to the lack of studies examining the relationship to general movements.…”
mentioning
confidence: 96%
“…This study adopted writhing movements at term-equivalent age as the analysis target of importance because the complexity is strongly associated with MDD 2 , 4 , 27 . Infantile spontaneous movements may show spatiotemporal characteristics analogous to spontaneous activity in the neocortex of the developing brain (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The early detection of high-risk infants for neurologic impairment is crucial for timely intervention. The identification of risk factors in preterm or low birth weight infants during the neonatal period facilitates early detection, leading to the initiation of early intervention and consequently, improving neurodevelopmental outcomes 1 , 2 . The General Movement Assessment (GMA), which was developed by Prechtl et al on infantile spontaneous movements, is recognized as a reliable and valid method for the early detection of high-risk infants 3 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation